Enhancing the learning of multi-level undergraduate Chinese language with a 3D immersive experience - An exploratory study. Issue 1 (14th March 2021) - Wang, Yanjun; Grant, Scott; Grist, Matthew
Abstract: The article reports on a study that incorporated an immersive 3 D virtual environment, created in Second Life (SL) into the curriculum of a Chinese program, including its development, implementation and evaluation. This innovation supplemented classroom teaching of Chinese language throughout one semester at a regional Australian university. Using the existing resource called Chinese Island (CI) created by a major urban Australian university, the primary aim of this study was to probe student's perceptions about the resource. Due to curriculum differences between two universities, customised language and culture learning tasks based on the learnt textbook content were designed on CI, with instructions and associated quizzes hosted in a private Moodle site—a widely-used learning management system (LMS) environment. Twenty-eight mixed-level undergraduate Chinese as a foreign language (CFL) students participated in a survey, and seven of these students were interviewed. The questionnaire and interview data were collected and analysed during the study. Following analysis, results indicated that students welcomed the experiential learning opportunity to explore Chinese culture and language outside the classroom afforded by CI. Anecdotal evidence suggested that students became more aware of the complicated pragmatic issues in real life communication. The survey results, including the participants' responses to open-ended questions, are discussed in this paper. Pedagogical implications and directions for further research are also considered.